Assessment of metal and metallcoid contamination in surface waters of the Pirapó river, Paraná State (PR), Brazil, and its environmental and human health risks (Research, Society and Development, 2025)
Heavy metal and metalloid contamination is one of the major threats to aquatic ecosystems and human health, particularly in river basins affected by urban, industrial, and agricultural activities. In this study, we assessed the presence and concentration of metals in surface water and fish tissues from the Pirapó River Basin (Paraná, Brazil), using inductively coupled plasma mass spectrometry (ICP-MS). Samples were collected at six strategically selected sites representing different levels of anthropogenic influence. The analyzed elements (Al, As, Hg, Zn, Se, Pb, Cd, Ni, Co, Mn, Fe, Cr, and Cu) were quantified after acid digestion and compared with national and international guideline values. The results revealed elevated concentrations of toxic metals, especially arsenic, mercury, selenium, cobalt, and manganese in fish tissues, indicating potential human health risks associated with fish consumption. These findings highlight the influence of anthropogenic sources on the environmental quality of the Pirapó River and reinforce the need for continuous monitoring and public policies aimed at mitigating metal contamination in the region.